Manpower Levels for Business with Various Recruitment Rates in the Ten Point State Space System through Stochastic Models - Arumugam, R; Rajathi, M (International Journal of Computer Sciences and Engineering, 2025)
Aim of the present study is to find the steady rate of crisis and steady state of probabilities with different situations which may be manpower, in irregular situations of complete availability, moderate availability and zero availability inside the case of manpower, business and recruitment. The various states have been discussed under the different assumptions that the transition from one state to another both business and manpower arise in exponential time with different parameters